Eroding trust in teacher professionalism: An ethnomethodological analysis of radio interviews with Czech experts on education - Tůma, František; Píšová, Michaela; Černá, Monika (My University, 2020)
Schools and teachers have been subject to a number of debates and often face contradictory demands. In this study we analyse radio interviews with three Czech experts on education. Building on ethnomethodology, namely conversation analysis and membership categorisation analysis, the study was guided by two research questions: (1) What practices and membership categorisation devices do the experts employ when speaking of Czech education and schools? and (2) How do the experts relate to teacher professionalism when characterising Czech education? The analysis shows how the expert’s credibility is negotiated, how they problematise gaining fundamental knowledge and skills at schools and situate the learning of “important things” outside school, and how they claim that Czech teachers teach badly while downgrading positive results of Czech schooling. This way the experts cast doubt on basic characteristics of teacher professionalism and thus undermine trust in the professional project in teaching.
Podrývání důvěry v profesionalismus učitelů: Etnometodologická analýza rozhlasových rozhovorů s experty na vzdělávání
Keywords: the professional project; teachers; trust; experts on education; radio interviews; ethnomethodology; profesionální projekt; učitelé; důvěra; experti na vzdělávání; rozhlasové rozhovory; etnometodologie